2006
DOI: 10.2466/pr0.99.3.739-742
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Religiosity with Academic Dishonesty in a Sample of College Students

Abstract: This study was conducted to estimate the relationship between academic dishonesty and religiosity in a convenient sample of college students. Scores on the Santa Clara Strength of Religious Faith Questionnaire and the Academic Practices Survey were correlated for 70 undergraduate students. Overall, religiosity and academic dishonesty were not significantly related. However, follow-up analyses by sex indicated that this association was significant for women but not men. Research should be conducted to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 7 publications
2
12
0
1
Order By: Relevance
“…In addition, we also found no statistically significant association between either religious affiliation or the stated importance of religion and student academic misconduct. This finding supports other studies that found no direct association between religious identity and belief and moral behaviors such as academic cheating (Huelsman et al, 2006;Smith et al, 1972). Nonetheless, it does not answer the question whether there is a relationship between religious behavior and academic integrity noted by other scholars (Bloodgood et al, 2008;Burton et al, 2011;Huelsman et al, 2006;Perrin, 2000;Rettinger & Jordan, 2005).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In addition, we also found no statistically significant association between either religious affiliation or the stated importance of religion and student academic misconduct. This finding supports other studies that found no direct association between religious identity and belief and moral behaviors such as academic cheating (Huelsman et al, 2006;Smith et al, 1972). Nonetheless, it does not answer the question whether there is a relationship between religious behavior and academic integrity noted by other scholars (Bloodgood et al, 2008;Burton et al, 2011;Huelsman et al, 2006;Perrin, 2000;Rettinger & Jordan, 2005).…”
Section: Discussionsupporting
confidence: 49%
“…This finding supports other studies that found no direct association between religious identity and belief and moral behaviors such as academic cheating (Huelsman et al, 2006;Smith et al, 1972). Nonetheless, it does not answer the question whether there is a relationship between religious behavior and academic integrity noted by other scholars (Bloodgood et al, 2008;Burton et al, 2011;Huelsman et al, 2006;Perrin, 2000;Rettinger & Jordan, 2005). Further research is needed to examine the relationship between religious beliefs and students' actual cheating behaviors.…”
Section: Discussionmentioning
confidence: 38%
“…However, as such, it has served as a pilot study in this research area. Further representative studies will be conducted in the future with appropriate sample size and additional independent factors like the role of socio-economic status [34], religion and religiosity [35] on academic integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies found that people with high intrinsic religiosity are less likely to engage in unethical behaviour (Arli & Tjiptono, 2014;Huelsman, Piroch, & Wasieleski, 2006;Longenecker, McKinney, & Moore, 2004;Randolph-Seng & Nielsen, 2007;Vitell et al, 2006).…”
Section: Religiositymentioning
confidence: 99%